Analysis on Fermentation Quality, Chemical Composition and Bacterial Communities of Corn Straw and Soybean Straw Mixed Silage - Zhifei Zhang; Kailing Zhao; Shuli Yang; Li Min; Xiong Tong; Weidong Chen; Dagang Li (Fermentation, 2023)
In this study, the effects of mixed silage on the fermentation quality, chemical composition and bacterial communities of corn straw and soybean straw were assessed. Corn straws, soybean straws or a mixture of corn straws and soybean straws in a 1:1 mass ratio were uniformly mixed and processed using the same method to produce bagged silage weighing 50 kg per bag. At days 0, 14 and 60 of the fermentation process, the nutritional composition and fermentation quality indicators of each group were measured. A complete factorial design to assess the effect of the ensiling time, types of fermented straw (treatment group) and their interactions on the assessed parameters was performed. In addition, metabolomics sequencing and microbial community analysis were performed on the samples on the 60th day of fermentation. Compared with the corn straw group and the soybean straw group, the silage fermentation quality of the corn straw–soybean straw group is better, which is reflected in higher crude protein rate (p < 0.05), higher lactic acid content (p < 0.05) and lower ammonia nitrogen content (p < 0.05). The combined analysis of differential microbial taxa (species level) and differential metabolites revealed a positive correlation between certain bacterial species, such as manihotivorans, brevis and zeae, and significantly downregulated metabolites, such as pyrocatechol and N-benzoyltyramine. Similarly, positive correlations were observed between certain bacterial species, such as dublinensis, marcescens and agglomerans, and upregulated metabolites, such as D-xylonic acid and neochlorogenic acid. These findings suggest that the key microbial–metabolite pathways identified are responsible for the good fermentation quality observed during mixed fermentation of corn straw and soybean straw at a 1:1 mass ratio.